Verzeichnis der in den Supplikenregistern der Pönitentiarie Leos X. vorkommenden Personen, Kirchen und Orte des Deutschen Reiches (1513-1521) : Band 1: Text. Band: 2 Indices. - Schmugge, Ludwig (De Gruyter, 2016)
"Repertorium Poenitentiariae Germanicum" is an edition of Latin Regesta from the supplication registers of the Penitentiary, the supreme Papal tribunal on penance and dispensations, during the late Middle Ages. Together with "Repertorium Germanicum," it represents a further major source for scholarly research on the medieval German Empire of the 15th century.